POEMS Syndrome Showing Left Ventricular Dysfunction and Extracellular Edema Assessed by Cardiac Magnetic Resonance Imaging - Takahashi, Yumi; Iwano, Hiroyuki; Nakano, Ippei; Fukushima, Arata; Naya, Masanao; Shimizu, Ai; Matsuno, Yoshihiro; Oyama-Manabe, Noriko; Anzai, Toshihisa (Internal Medicine, 2019)
Although cardiac involvement is rare in polyneuropathy, organomegaly, endocrinopathy, M protein, and skin changes (POEMS) syndrome, the clinical course becomes considerably worse on complication with cardiac lesions. The increased release of various cytokines has been observed in the pathogenesis of POEMS syndrome, and serum vascular endothelial growth factor (VEGF) levels are known to be associated with the disease activity. We herein report a patient with POEMS syndrome who showed left ventricular systolic dysfunction and was treated with lenalidmide therapy. Of note, the reduction in extracellular edema in the left ventricular wall was clearly visualized by changes in the native T1 values and extracellular volumes on cardiac magnetic resonance imaging.